Alcohol amination with ammonia catalyzed by an acridine-based ruthenium pincer complex: a mechanistic study - Ye, Xuan; Plessow, Philipp N.; Brinks, Marion K.; Schelwies, Mathias; Schaub, Thomas; Rominger, Frank; Paciello, Rocco; Limbach, Michael; Hofmann, Peter (Journal of the American Chemical Society, 2014)
The mechanistic course of the amination of alcohols with ammonia catalyzed by a structurally modified congener of Milstein’s well-defined acridine-based PNP-pincer Ru complex has been investigated both experimentally and by DFT calculations. Several key Ru intermediates have been isolated and characterized. The detailed analysis of a series of possible catalytic pathways (e.g., with and without metal-ligand cooperation, inner- and outer-sphere mechanisms) leads us to conclude that the most favorable pathway for this catalyst does not require metal-ligand cooperation.